2000
DOI: 10.1002/1521-396x(200011)182:1<307::aid-pssa307>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silicon as an Effective Material for Thermal Isolation on Bulk Crystalline Silicon

Abstract: Highly porous silicon has been successfully used to create thermally isolated local areas on bulk crystalline silicon, for the fabrication of silicon integrated sensors. Heat distribution and heat transfer have been simulated by using finite element analysis with the ANSYS software. Three cases were compared: the case of bulk crystalline silicon, the case of porous silicon and that of free standing polycrystalline silicon membranes. A flow sensor of the thermal type using porous silicon isolation has been desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…Passive photonic devices designed in silicon such as waveguides, couplers and splitters have been reported. 185 It has been shown that micro-and meso-PSi layers are excellent materials for local thermal isolation on bulk silicon 106,186 and for fabrication of micro-hotplates for low-power sensors. [187][188][189] Micro-and meso-PSi could also be used as isolation material for radio-frequency (rf) applications because of its high resistivity and compatibility with modern very-largescale-integration IC technology.…”
Section: Fields Of Porous Si Applicationsmentioning
confidence: 99%
“…Passive photonic devices designed in silicon such as waveguides, couplers and splitters have been reported. 185 It has been shown that micro-and meso-PSi layers are excellent materials for local thermal isolation on bulk silicon 106,186 and for fabrication of micro-hotplates for low-power sensors. [187][188][189] Micro-and meso-PSi could also be used as isolation material for radio-frequency (rf) applications because of its high resistivity and compatibility with modern very-largescale-integration IC technology.…”
Section: Fields Of Porous Si Applicationsmentioning
confidence: 99%
“…[19][20][21] For thermoelectrics, the effectiveness of a material is evaluated by its thermoelectric figure of merit (ZT), defined as ZT ¼ S 2 rT/k, where S, r, k, and T represent Seebeck coefficient, electrical conductivity, thermal conductivity, and absolute temperature, respectively. 22 In semiconducting thermoelectric materials, k can be further split into the lattice contribution k L and electronic contribution k E .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that micro-and meso-PSi layers are excellent materials for local thermal isolation on bulk silicon (Nassiopoulou and Kaltsas 2000;Lysenko et al 2002) and for fabrication of micro-hotplates for low-power sensors (Maccagnani et al 1998(Maccagnani et al , 1999Tsamis et al 2003). Experiment has shown that the technology of silicon porosification is alternative for silicon on insulator (SOI) and silicon on sapphire (SOS) technologies.…”
Section: Fields Of Porous Silicon Applicationsmentioning
confidence: 99%